KOSMOLOGI DALAM EKSPRESI RITUS SIKLUS HIDUP MUSLIM JAWA BARAT - Nulhasanah, Lisan; Hasan, Hidayat; Hidayat, Asep Ahmad; Supendi, Usman; Tohir, Ajid (FASTABIQ: JURNAL STUDI ISLAM, 2023)
The research aims to understand cosmological relationships both in the context of space and time, such as apamali or taboos in the life cycle which includes cultural customs, rituals: birth, circumcision and marriage in the West Javanese Sundanese community, both in the northern coastal communities (Cirebonan) and inlad. (mountains) like in Tatar Priangan (West Java settlement). The research methode used in thiss research in an antrhropological research method woth alibrary study approach with a content analysis method (Symbolic interpretation) of data from the anthropological method. The research resultas show that the life cycle of the people of West Java both in Sunda-Priangan and Cirebon, which represents the people of the North Coast of Java (West), implies the existence of four importans stages, namely pregnancy, birth, circumcision and marriage. Each of these stages has an important symbolic meaning in building identity and social ralations in West Java society which contains the meaning of the slametan cultural tradition in these cycles related to the subtsnce of belief or religion (Islam).  Keywords: Cosmology; Pregnancy; Birth; Circumcision; Marriage